The interaction of ABA and ROS in plant growth and stress resistances - Li, Shenghui; Liu, Sha; Zhang, Qiong; Cui, Meixiang; Zhao, Min; Li, Nanyang; Wang, Suna; Wu, Ruigang; Zhang, Lin; Cao, Yunpeng; Wang, Lihu (Frontiers in Plant Science, 2022)
The plant hormone ABA (abscisic acid) plays an extremely important role in plant growth and adaptive stress, including but are not limited to seed germination, stomatal closure, pathogen infection, drought and cold stresses. Reactive oxygen species (ROS) are response molecules widely produced by plant cells under biotic and abiotic stress conditions. The production of apoplast ROS is induced and regulated by ABA, and participates in the ABA signaling pathway and its regulated plant immune system. In this review, we summarize ABA and ROS in apoplast ROS production, plant response to biotic and abiotic stresses, plant growth regulation, ABA signal transduction, and the regulatory relationship between ABA and other plant hormones. In addition, we also discuss the effects of protein post-translational modifications on ABA and ROS related factors.